Sosialisasi Permainan Bola Voli Serpassring Pada Kegiatan KKG Guru Penjas Di Kecamatan Karangpucung - Kusmiyati Kusmiyati; Dian Imam Saefulah; Diyah Kusuma Ningrum (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
Community service is non-formal education for physical education teachers in schools, through educational activities, and educational outreach that can support community development. Education for the community is one of the implementations of the tri-dharma of higher education. Community service through the socialization of the Serpassring Volleyball Game at Physical Education Teachers' Kkg Activities in Karangpucung District is an effort to: (1) find out and provide a level of understanding of sports human resource management knowledge for Physical Education teachers in schools in Karangpucung District; (2) Knowing and describing the potential of sports human resources in Karangpucung District schools. This Community Service aims to provide education for physical education teachers in each school about understanding the Serpassring Volleyball Game and identifying talent from an early age in schools to create a generation of high achievers. As a result of this community service, there is an increase in knowledge about skills in preparing training programs and understanding of identifying children's talents in looking for athletes in schools, especially in the field of Serpassring Volleyball.